Characterization of the Plant‒Soil feedback index in alpine meadow degradation and recovery: A field experiment - Yandi, She; Tao, Ma; Huakun, Zhou; Honglin, Li; Zhonghua, Zhang; Li, Ma; Ruimin, Qin; Hongye, Su; Tao, Chang; Jingjing, Wei; Xue, Hu (Frontiers in Environmental Science, 2023)
Most plant‒soil feedback studies have been conducted on the mechanism by which soil directly influences plant growth performance and mostly in indoor pot experiments; however, it is unclear how plant‒soil feedback is influenced by plant, soil and microbial diversity in grassland ecosystems in alpine meadows with high plant diversity. In this study, plant‒soil feedback patterns were investigated by analyzing plant, soil and microbial characteristics across seven gradients in the time series from light degradation to 10-years of recovery, classified into three categories: ecosystem multifunctionality, biotic and abiotic factors, and comparing the strength and magnitude of plant‒soil feedback in alpine meadows of degradation stages and years of recovery. The results showed that the plant-soil feedback relationships in alpine meadows differed significantly in three aspects: ecosystem multifunctionality, biotic and abiotic factors in the degradation stage and recovery years, and under the degradation gradient, ecosystem multifunctionality decreased from 0.34 to −0.99 with the deepening of degradation, biotic factors increased from −0.17 to 0.09, and abiotic factors increased from −0.17 to 0.15, while in the recovery gradient, ecosystem multifunctionality showed a trend of increasing and then decreasing with increasing recovery years, while biotic and abiotic factors showed fluctuating changes. The plant-soil feedback index indicated that the strength and direction of plant-soil interactions during degradation and recovery were different, and the positive feedback effect was 0.34 and 0.38 in the early stage of degradation and recovery, respectively, which were greater than the negative feedback effect. With the deepening of degradation, the negative feedback effect became more and more obvious, and at the stage of extreme degradation, the negative feedback effect reached −0.99, which was much larger than the positive feedback effect. However, with the increase of the recovery years, the positive feedback effect gradually weakened, and finally all of them were negative feedback effects at 10-years of recovery. This study provides a scientific basis for understanding plant-soil feedback in alpine meadow ecosystems and indicates the direction for the next scientific recovery of alpine meadows.